This preview shows page 1. Sign up to view the full content.
Unformatted text preview: (f) If f ( n ) = ( g ( n )) and h ( n ) = ( g ( n )) then f ( n ) h ( n ) = ( g ( n )). (g) If f ( n ) = ( g ( n )) and h ( n ) = ( g ( n )) then f ( n ) + h ( n ) = ( g ( n )). (h) If f ( n ) = O ( g ( n )) then g ( n ) = ( f ( n )). (i) If f ( n ) = ( g ( n )) then g ( n ) = ( f ( n )) (j) If f ( n ) = log a ( n ) for a > 2 then f ( n ) n = ( log 2 ( n )). 1...
View
Full
Document
 Spring '08
 Erickson

Click to edit the document details